Quality of cultural environment: problems of measurement - Ludmila Pronina (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the paper relates to the issues of life quality, including the quality of cultural environment which has been changing for the recent years. Its virtual part is actively developing, the real, traditional environment has been transformed and modernized. Quantitative indicators do not allow determining its quality parameters, so it is necessary to create a system of indicators and indices that characterize conceptual essence of cultural environment and determine its quality. The article is aimed at formation of aggregate of cultural environment quality indices. Research methods: analytical methods at junction of theory of culture and informology. The results: the approaches to measurement of cultural environment quality are disclosed; its basic components - information core, infofund, synchronic and diachronic inforelations are offered. The paper figures out the indicators and indices measuring the quality of virtual and real cultural environment and introduces author's indicators of cultural relevance as an information core relevance, infofund to the requirements, emphasized in various cultural requests (on cultural events, cultural environment and its quality) and cultural pertinence as a compliance with the cultural heritage of real needs of those who are interested in the heritage (individuals, social groups, social system, humanity as a whole).